Radicalising the Mainstream in Western Europe: The Far Right and Narratives of Islam in Contemporary and Historical Perspective (Springer Nature, 2025)
This Open Access book offers a mixed-method approach to analysing anti-Muslim narratives in interactions between the far right and the Western European mainstream. By exploring narratives that portray Islam as inherently other, the essays in this collection interrogate the effects of such narratives on the targeted group and mainstream society. Authors explore mechanisms, such as historical othering, media agenda building, and online mobilization of the far right, and harness historical analysis, media content, social media network analyses and qualitative surveys, to propose that the effects of such media narratives are far from purely symbolic.